Noncentrosomal microtubules in C. elegans epithelia. Issue 4 (6th April 2016) - Quintin, Sophie; Gally, Christelle; Labouesse, Michel
Summary: The microtubule cytoskeleton has a dual contribution to cell organization. First, microtubules help displace chromosomes and provide tracks for organelle transport. Second, microtubule rigidity confers specific mechanical properties to cells, which are crucial in cilia or mechanosensory structures. Here we review the recently uncovered organization and functions of noncentrosomal microtubules in C. elegans epithelia, focusing on how they contribute to nuclear positioning and protein transport. In addition, we describe recent data illustrating how the microtubule and actin cytoskeletons interact to achieve those functions. genesis, 2016. © 2016 Wiley Periodicals, Inc. genesis 54:229–242, 2016. © 2016 Wiley Periodicals, Inc.